The role of the cytoskeleton in the polarisation of Marchantia polymorpha spores - Attrill, ST (2023)
All multicellular land plants start life as a single cell. By polarising – developing asymmetry – and dividing asymmetrically, this single cell can form two distinct cell lineages and establish the first plant body axis. How these cells establish polarity from a non-polar state is little known. A novel single-celled polarity system is the spore of the liverwort Marchantia polymorpha. This haploid cell polarises, by unknown mechanisms, and divides asymmetrically to form a proliferating stem cell and differentiated rhizoid cell. My project aimed to define the dynamics of the cytoskeleton - microtubules and actin filaments - in the establishment of spore polarity. By live timelapse imaging of spores expressing fluorescent reporters, I show that the nucleus migrates from the cell centre to the basal cortex to orient the first asymmetric division. Movement of the nucleus is led by a microtubule organising centre (MTOC) nucleating a dense astral array. An actin filament network also forms in the space between the migrating nucleus and the basal cortex. These data support the hypothesis that the cytoskeleton is required for nuclear migration during spore polarisation. Cytoskeleton organisation and dynamics requires tight regulation by proteins such as the microtubule severing enzyme, katanin. By mutating katanin, I discovered that katanin severing is required for MTOC formation and microtubule organisation in M. polymorpha. Collectively these findings propose that microtubules, MTOCs, actin filaments and possibly katanin are required for the establishment of spore polarity and to orient the first asymmetric division plane, thereby defining the first apical-basal body axis of M. polymorpha.